Understanding what Australians find fearful and hopeful about climate change through qualitative approaches - Matthew I. Mackay; Anna Klas; Emily J. Kothe; Kate Barford; Julian W. Fernando; Mathew Ling (PLoS ONE, 2026)
Future-oriented emotional appeals, such as fear or hope, may be more effective in increasing climate action when they reflect the specific fears and hopes of the target population. However, qualitative evidence on what people find uniquely fearful and uniquely hopeful about climate change remains limited. To address this gap, an online qualitative survey asked 299 Australians ( M age = 33.09, SD age = 12.14) to identify what they found fearful and hopeful about climate change. Through inductive thematic analysis, three themes reflected Australians’ fear: (1) ‘Change and Instability’, (2) ‘Inaction and Negligence by Government, Large Corporations, and Others’, and (3) ‘Intergenerational Impacts and Legacy’. Additionally, three themes reflected Australians’ hope: (1) ‘Changing Attitudes and Changing Pro-environmental Habits’, (2) ‘Progress, Technology, Sustainability, and Innovation’, and (3) ‘An Opportunity for Change’. While some elements of what Australians find fearful or hopeful may be unique (e.g., bushfires), others (e.g., intergenerational impacts) align with global concerns. These insights offer valuable guidance for designing interventions that aim to foster fear and hope to promote climate action.